A Muscle-First, Electromechanical Hybrid Gait Restoration System in People With Spinal Cord Injury - Nandor, Mark; Kobetic, Rudi; Audu, Musa; Triolo, Ron; Quinn, Roger (Frontiers in Robotics and AI, 2021)
The development of a hybrid system for people with spinal cord injuries is described. The system includes implanted neural stimulation to activate the user's otherwise paralyzed muscles, an exoskeleton with electromechanical actuators at the hips and knees, and a sensory and control system that integrates both components. We are using a muscle-first approach: The person's muscles are the primary motivator for his/her joints and the motors provide power assistance. This design philosophy led to the development of high efficiency, low friction joint actuators, and feed-forward, burst-torque control. The system was tested with two participants with spinal cord injury (SCI) and unique implanted stimulation systems. Torque burst addition was found to increase gait speed. The system was found to satisfy the main design requirements as laid out at the outset.